Russell's theory of incomplete symbols: its significance in his philosophy of mathematics - Mukhopadhyay, Arnab Kumar (Kolkata: Knowledge Bank, 2012)
Study on the mathematical philosophy and logic of Bertrand Russell, 1872-1970, a British mathematician, logician and philosopher.
Includes bibliographical references and index.
In Bengali; includes passages in English.
Keywords: RUSSELL, BERTRAND -- 1872-1970.; MATHEMATICS -- PHILOSOPHY; LOGIC